Fruits, Ice and Coffee in 17th Century Persia - Chardin, Sir John (Petits Propos Culinaires, 1999)
An extensive extract from Sir John Chardin’s Travels in Persia. This extract concerns types of fruit encountered, ice and its culinary uses, coffee drinking and coffee houses.